Mice with an autism‐associated R451C mutation in neuroligin‐3 show a cautious but accurate response style in touchscreen attention tasks. (2nd July 2021) - Burrows, Emma L.; May, Carlos; Hill, Thomas; Churliov, Leonid; Johnson, Katherine A.; Hannan, Anthony J.
Abstract: One of the earliest identifiable features of autism spectrum disorder (ASD) is altered attention. Mice expressing the ASD‐associated R451C mutation in synaptic adhesion protein neuroligin‐3 (NL3) exhibit impaired reciprocal social interactions and repetitive and restrictive behaviours. The role of this mutation in attentional abnormalities has not been established. We assessed attention in male NL3 R451C mice using two well‐established tasks in touchscreen chambers. In the 5‐choice serial reaction task, rodents were trained to attend to light stimuli that appear in any one of five locations. While no differences between NL3 R451C and WT mice were seen in accuracy or omissions, slower response times and quicker reward collection latencies were seen across all training and probe trials. In the rodent continuous‐performance test, animals were required to discriminate, and identify a visual target pattern over multiple distractor stimuli. NL3 R451C mice displayed enhanced ability to attend to stimuli when task‐load was low during training and baseline but lost this advantage when difficulty was increased by altering task parameters in probe trials. NL3 R451C mice made less responses to the distractor stimuli, exhibiting lower false alarm rates during all training stages and in probe trials. Slower response times and quicker reward latencies were consistently seen in NL3 R451C mice in the rCPT. Slower response times are a major cognitive phenotype reported in ASD patients and are indicative of slower processing speed. Enhanced attention has been shown in a subset of ASD patients and we have demonstrated this phenotype also exists in the NL3 R451C mouse model. Abstract : NL3 mice displayed enhanced ability to attend to stimuli when task‐load was low but lost this advantage when difficulty was high.